2017
DOI: 10.1111/ejh.12895
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of BKPyV reactivation and risk of hemorrhagic cystitis after allogeneic hematopoietic stem cell transplantation

Abstract: Monitoring of BKPyV-DNA by real-time PCR after initiation of conditioning, regularly performed in clinical practice, can be a crucial tool for the early identification of patients with higher risk of BKPyV-associated HC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Erard et al [17] showed in a multivariate model that plasma viral load of more than 10 4 copies/mL was associated with developing HC in allogeneic hematopoietic stem cell transplant recipients. Höller et al [33] could not detect a predictive cutoff for plasma viral load in a recent study, but they indicated that the presence of viremia might itself predict BKV-associated morbidity. Interestingly, we detected a lower threshold (2 log 10 ) for BK-related HC in our prospective study, which might be related to the limited number of patients included in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Erard et al [17] showed in a multivariate model that plasma viral load of more than 10 4 copies/mL was associated with developing HC in allogeneic hematopoietic stem cell transplant recipients. Höller et al [33] could not detect a predictive cutoff for plasma viral load in a recent study, but they indicated that the presence of viremia might itself predict BKV-associated morbidity. Interestingly, we detected a lower threshold (2 log 10 ) for BK-related HC in our prospective study, which might be related to the limited number of patients included in our study.…”
Section: Discussionmentioning
confidence: 95%
“…While the risk factors for the development of BKPyV-HC identified in previous studies were not always consistent, most studies found a strong association between the detection of BKPyV in the urine and serum and development of BKPyV-HC. [13][14][15][24][25][26][27][28][29] In addition, the timing of the development of BKPyV viruria, the viral load, and an increase in viremia have been correlated with the development of BKPyV-HC. Patients have been reported to develop HC as early as 34 days after allogeneic SCT.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has been demonstrated that high-level BKPyV viruria and viremia have been found to be predictive factors for post-allogeneic SCT BKPyV-HC in both pediatric and adult populations. [13][14][15] Other studies have indicated that plasma BKPyV monitoring did not demonstrate early detection or rising plasma BKPyV levels predicts for BKHC. 16 While it is increasingly clear that there is still no consensus on whether urine or plasma levels of BKPyV should be tested, what levels are predictive of BKPyV-HC, and when testing should be conducted, it has been demonstrated that underlying malignancy, conditioning regimen, and HLA match status showed significant associations with BKPyV replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis is confirmed by quantitatively measuring viral copies in plasma or urine. It has been shown that being an asymptomatic carrier of BK virus after HSCT is a risk factor for AKI, especially when viremia is detectable [7].…”
Section: Ivyspringmentioning
confidence: 99%